2023
DOI: 10.1111/jvim.16717
|View full text |Cite
|
Sign up to set email alerts
|

Development of a reliable clinical assessment tool for meningoencephalitis in dogs: The neurodisability scale

Abstract: Background Meningoencephalitis of unknown origin (MUO) comprises a group of debilitating inflammatory diseases affecting the central nervous system of dogs. Currently, no validated clinical scale is available for the objective assessment of MUO severity. Objectives Design a neurodisability scale (NDS) to grade clinical severity and determine its reliability and whether or not the score at presentation correlates with outcome. Animals One hundred dogs with MUO were included for retrospective review and 31 dogs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 34 publications
5
15
0
Order By: Relevance
“…Noteworthily, no other factor recognized at presentation was signi cantly linked with the short-term prognosis. On the other hand, the neurological scales do not appear to be associated with either mid-term or long-term prognosis, what is consistent with the ndings of previous studies [1,23].…”
Section: Discussionsupporting
confidence: 92%
“…Noteworthily, no other factor recognized at presentation was signi cantly linked with the short-term prognosis. On the other hand, the neurological scales do not appear to be associated with either mid-term or long-term prognosis, what is consistent with the ndings of previous studies [1,23].…”
Section: Discussionsupporting
confidence: 92%
“…The NDS has been recently proposed as a reliable clinical scale for initial assessment of patients with MUO. 11 Our study found an association between the NDS score and increased risk of death within the 6 months after diagnosis, relapse, and incomplete resolution of clinical signs within that time. In human patients, higher baseline score in the expanded disability status scale (EDSS), the most commonly used clinical outcome measure for patients with MS, is predictive for worse outcomes.…”
Section: Discussionsupporting
confidence: 51%
“…The following data were extracted from the medical records: age, sex, neuter status, breed and duration of the clinical signs and survival information. The findings of the neurological examination recorded on the patient files were used to retrospectively assign the neurodisability scale (NDS) ( 16 ) score for each dog (calculated by the same assessor in all dogs).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a neurodisability scale (NDS) has been shown to be a reliable clinical assessment tool for dogs with MUO. Initial data from a small population of dogs was unable to show an association between this score and outcome ( 16 ) but retrospective use of this scale in a large population of dogs with MUO showed an association between higher NDS score and death at 6 months as well as long-term relapse ( 13 ).…”
Section: Introductionmentioning
confidence: 99%